Multisensor systems for gas analysis: optimization of arrays for classification of pharmaceutical products - Kruglenko, I.V.; Snopok, B.A.; Shirshov, Yu.M.; Rowell, F.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
In the present work, the use of the cluster analysis method in the “fuzzy logic” concept for the optimization of the cross-selective sensor arrays (“electronic nose”, EN) is considered. This approach enables to purposefully form the sensor arrays with definite chemical functionality optimized for the solution of the specific applied problems. The criteria of the optimization of the sensor response, number and type of the sensor elements are considered with the goal to improve the classification of widely used pharmaceutical products. The optimization of EN array in the kinetic mode and selection of the most informative part of the sensor response enabled to reduce the analysis time, and also the number of sensors in array, to improve the discriminatory capability of the whole array. Being based on the analysis of response kinetic peculiarities, the physical mechanisms determining the peculiarities of adsorption-desorption processes at the interface have been considered.